2014
DOI: 10.1177/1010539514524817
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Healthy Lifestyle and Hospital Utilization Among Adults With Diabetes

Abstract: The aim of this study was to investigate whether adopting healthy lifestyle habits, such as engaging in leisure time physical activity (LTPA), adopting recommended dietary patterns, and not smoking, are associated with reduced hospitalizations over 1 year among adults with diabetes. We analyzed data from a national sample of people aged 18 years and above with self-reported physician-diagnosed diabetes (n = 664) through linkage to the 2001 National Health Interview Survey in Taiwan and the 2002 National Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…There was no evidence that the PA intervention reduced LOS. In cross‐sectional and observational studies of older adults, regular PA has been shown to significantly reduce healthcare use and costs, including LOS . However, a recent Cochrane review reported that there was only a nonsignificant trend toward fewer individuals being admitted to the hospital with exercise in randomized controlled trials of exercise‐based interventions with 6 months of follow‐up or longer than with usual medical care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no evidence that the PA intervention reduced LOS. In cross‐sectional and observational studies of older adults, regular PA has been shown to significantly reduce healthcare use and costs, including LOS . However, a recent Cochrane review reported that there was only a nonsignificant trend toward fewer individuals being admitted to the hospital with exercise in randomized controlled trials of exercise‐based interventions with 6 months of follow‐up or longer than with usual medical care.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that a structured moderate‐intensity physical activity (PA) program reduced major mobility disability more than a health education (HE) program did over an average follow‐up of 2.6 years in older adults at risk of disability . Another potential benefit of a PA intervention that observational studies of older persons have suggested is less risk of hospitalization and fewer admissions and bed stays . However, in the Lifestyle Interventions and Independence for Elders (LIFE) Study, a randomized controlled trial, a nonsignificant difference was found in the overall proportion of randomized participants reporting hospitalizations at assessment visits between PA (48.4%) and HE (44.1%) group participants (risk ratio = 1.10, 95% confidence interval (CI) = 0.99–1.22); a difference that the LIFE Data Safety and Monitoring Board scrutinized closely during follow‐up as a safety outcome .…”
mentioning
confidence: 99%
“…As a severe medical and social problem, obesity poses a harsh threat to public health for its potential association with a bundle of chronic diseases such as diabetes and hypertension. In recent decades, the risk of obesity and related chronic diseases have been intensively studied [ 1 4 ]; however, obesity and related chronic diseases in developing countries have been relatively neglected [ 5 ], though few developing countries are unaffected by these conditions. China, as a developing country, is experiencing a sharp economic growth and subsequently, a substantial increase in weight level, and is receiving an increasing amount of attention [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%